FAS vs. IFRS Impact Analysis in International Private Equity and Venture Capital Valuation Framework : Case Study - Virtanen, Jenny (My University, 2023)
It is mandatory for the public companies to publish their financial statements. After the year of 2005, all public companies in the EU are required to report their statement by using IFRS standards. The purpose of the study was to research which financial statement, FAS or IFRS, reports information that is more valuable from the private equity’s point of view and which shows greater value for the company. The empirical findings of the research provided value of three case compa-nies through creating additional information for the client about the FAS and IFRS differences based on the valuations and experts’ views. In the theoretical part the focus was on FAS, IFRS and International Private Equity and Venture Capital Valuation (IPEV). The main difference between FAS and IFRS were introduced and the IPEV valuation guidelines were stated from the most important parts from this thesis’s point of view. The limitations of the study focused on IFRS standards and discounted cash flow method and took into consideration the parts that are eliminated from the calculations. In the thesis the valuation framework and how the Discounted Cash Flow was used were described as a valuation method. This thesis has both quantitative and qualitative research methods. The calculations of the values used descriptive and inferential research methods and the interview was completed by using semi-structured base. The results of the study stated that adoption of IFRS has mostly positive outcome in the cases, from the private equity’s point of view. The amount of EBIT grew after the adoption of IFRS and conse-quentially the value of the case companies grew in two out of three cases. For example, there could be differences between sectors and because of some companies benefit from the adoption of IFRS standards more. The results of the thesis concluded that IFRS based numbers show better image of the firm to the investors since the value of the firm is greater.

Julkisten yhtiöiden on julkistettava tilinpäätöksensä. Vuoden 2005 jälkeen kaikkien EU:n julkisten yhtiöiden on raportoitava lausuntonsa IFRS-standardien mukaisesti. Tutkimuksen tarkoituksena oli selvittää, kumpi tilinpäätös, FAS vai IFRS, raportoi pääomasijoittamisen kannalta arvokkaam-paa ja yritykselle arvokkaampaa tietoa. Tutkimuksen avulla oli mahdollista luoda lisätietoa asiak-kaalle FAS:n ja IFRS:n eroista laskelmien ja asiantuntijoiden näkemysten perusteella. Teoreettisessa osassa painopiste oli FAS:ssa, IFRS:ssä ja kansainvälisessä pääomasijoitus- ja riski-pääoman arvostuksessa (IPEV). Pääasiallinen ero FAS:n ja IFRS:n välillä esiteltiin ja IPEV-arvostusohjeet esitettiin tämän opinnäytetyön kannalta tärkeimmistä osista. Tutkimuksen rajoitukset keskittyivät IFRS-standardeihin ja diskontatun kassavirran menetelmään, sekä huomioivat laskelmista pois jääneen osan. Neljännessä luvussa keskityttiin arvostuskehykseen ja siihen, miten diskontattua kassavirtaa käytettiin arvostusmenetelmänä. Tässä tutkielmassa on sekä kvantitatii-visia että kvalitatiivisia tutkimusmenetelmiä. Arvojen laskennassa käytettiin deskriptiivisiä ja päät-telymenetelmiä, mutta haastattelu toteutettiin puolistrukturoidun haastattelurungon avulla. Tutkimuksen tulosten perusteella voidaan todeta, että IFRS:n käyttöönotolla on pääosin positiivinen vaikutus pääomasijoittajan näkökulmasta. Liikevoiton määrä kasvoi IFRS:n käyttöönoton jälkeen ja sitä kautta tutkimuskohteiden arvo kasvoi kahdessa kolmesta tapauksesta. Esimerkiksi toimialojen välillä voi olla eroja ja tämän vuoksi jotkut yritykset hyötyvät enemmän IFRS-standardien käyttöönotosta. Tutkimuksen johtopäätöksenä voidaan todeta, että IFRS-pohjaiset luvut antavat sijoittajille paremman kuvan yrityksestä, koska yrityksen arvo on suurempi.
Keywords: financial statements; International Financial Reporting Standards; valuation; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance